Financial Development, Financial Inclusion, and Poverty Reduction in Nigeria - Hassan, Bello; Gbemisola, Olajide (AFEBI Economic and Finance Review, 2024)
This study explores the intertwined roles of financial development and financial inclusion in alleviating poverty, with a focus on Nigeria. Financial development enhances capital allocation and economic growth, while financial inclusion ensures access to affordable financial services for marginalized populations. Together, they support poverty reduction by promoting investment, entrepreneurship, and risk management. Despite Nigeria's progress with initiatives like the National Financial Inclusion Strategy, challenges such as poverty, unemployment, and inequality persist, hindering widespread benefits. Microfinance institutions and digital financial services, like mobile money, have made strides in reaching underserved regions. However, barriers such as high interest rates, low digital literacy, and unequal access to financial services remain significant. This study examines statistical trends and the effectiveness of financial strategies in fostering sustainable economic growth and poverty alleviation. It underscores the need for enhanced infrastructure, digital education, and trust in financial systems to achieve inclusive development. By addressing these challenges, policymakers and institutions can unlock the full potential of financial inclusion and development as pivotal tools for poverty reduction in Nigeria. Keywords: Financial development, Financial inclusion, Poverty alleviation, Microfinance institutions and Digital financial services